ANALISIS PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA ARTIKEL TERINDEKS SINTA - Heryana, Regina Putri; Luthfi, Dwi; Fitriana, Fitriana; Santoso, Rachmat Agus (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
Basically, maximizing profits is the company's main goal. Tax avoidance is one way to maximize profits. Tax avoidance is a legal action that takes advantage of loopholes in the law so that companies can pay small amounts of tax. This research aims to analyze and review previous research regarding the relationship between profitability and leverage on tax avoidance. This research uses a qualitative method with a literature review approach to strengthen arguments with information collected in articles published in the national journal SINTA with a sample of 25 articles. The results of this study prove that profitability and leverage have no effect on tax avoidance